2019
DOI: 10.1128/iai.00541-18
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Bite-Induced Controlled Human Malaria Infection with Plasmodium vivax or P. falciparum Generates Immune Responses to Homologous and Heterologous Preerythrocytic and Erythrocytic Antigens

Abstract: Seroepidemiological studies on the prevalence of antibodies to malaria antigens are primarily conducted on individuals from regions of endemicity. It is therefore difficult to accurately correlate the antibody responses to the timing and number of prior malaria infections. This study was undertaken to assess the evolution of antibodies to the dominant surface antigens of Plasmodium vivax and P. falciparum following controlled human malaria infection (CHMI) in malaria-naive individuals. Serum samples from malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…MSP-1 is another viable blood stage candidate. In the CHMI study described earlier (56), 50% of volunteers infected with P. vivax had antibodies to PfMSP-1 while 67% of those infected with P. falciparum recognized PvMSP-1 on day 28 after infection. Far lower frequencies of cross-reactivity were observed in other studies.…”
Section: Erythrocytic Targetsmentioning
confidence: 84%
See 3 more Smart Citations
“…MSP-1 is another viable blood stage candidate. In the CHMI study described earlier (56), 50% of volunteers infected with P. vivax had antibodies to PfMSP-1 while 67% of those infected with P. falciparum recognized PvMSP-1 on day 28 after infection. Far lower frequencies of cross-reactivity were observed in other studies.…”
Section: Erythrocytic Targetsmentioning
confidence: 84%
“…These findings suggested that PvCSP and PfCSP might share cross-reactive T-cell epitopes, while there was no evidence of heterologous antibody responses. In contrast, deliberate infection of naïve volunteers with either P. falciparum or P. vivax by mosquito bite gave rise to heterologous antibody responses to CSP from each species (56). In both groups, 61% of volunteers had antibodies that cross-reacted with the heterologous CSP antigen.…”
Section: Pre-erythrocytic Targetsmentioning
confidence: 95%
See 2 more Smart Citations
“…Compelling evidence suggests cross-protection between malaria parasite species due to species-transcending immunity [41,42]. We wondered whether the lack of ability to control the P. vinckei parasitaemia towards the end of the mixed infection of P. vinckei and P. yoelii may be due to the phenomenon of "original antigenic sin" [43] rendering the acquisition of antibodies specific to P. vinckei sub-optimal due to the larger quantity of P. yoelii antigen present in the early stages of the infection.…”
Section: P Chabaudimentioning
confidence: 99%